1987
DOI: 10.3109/13813458709075024
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthèse et métabolisme de l'histamine dans le système nerveux central deCarcinus maenas

Abstract: The central nervous system of Carcinus maenas synthesizes radioactive histamine when incubated in the presence of [14C] histidine and pyridoxal-5' phosphate. This biosynthesis increases linearly as a function of the amount of enzyme and the incubation time. It is not effected by heart, muscle or hepatopancreas extracts nor by haemolymph. Thus histamine appears to be synthesized mainly in the nervous system. The latter is also the seat of carcinine (beta-alanylhistamine) biosynthesis. Since carcinine seems to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…The presence of the histidine decarboxylase in neural structures such as thoracic ganglia, brain ganglia and eyestalks of the crab was established by measuring the conversion of [ 14 C]histidine to radioactive HA in the presence of pyridoxal-5 phosphate (Arnould, 1987). Immunohistochemical studies demonstrated the presence of HA-like reactivity in lobster stomatogastric ganglion neurons (Dando and Selverston, 1972;Sigvart and Mulloney, 1982;Mulloney and Hall, 1991), thoracic and subesophageal ganglia (Mulloney and Hall, 1991), olfactory lobe (Orona et al, 1990), median protocerebrum, and deutocerebrum and tritocerebrum (Langworthy et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of the histidine decarboxylase in neural structures such as thoracic ganglia, brain ganglia and eyestalks of the crab was established by measuring the conversion of [ 14 C]histidine to radioactive HA in the presence of pyridoxal-5 phosphate (Arnould, 1987). Immunohistochemical studies demonstrated the presence of HA-like reactivity in lobster stomatogastric ganglion neurons (Dando and Selverston, 1972;Sigvart and Mulloney, 1982;Mulloney and Hall, 1991), thoracic and subesophageal ganglia (Mulloney and Hall, 1991), olfactory lobe (Orona et al, 1990), median protocerebrum, and deutocerebrum and tritocerebrum (Langworthy et al, 1997).…”
Section: Introductionmentioning
confidence: 99%